SIMULATION TECHNIQUE IN SPEAKING FLUENCY OF THE STUDENTS AT SMA MUHAMMADIYAH 7 MAKASSAR - Saputra, Wongso Adi (JKIP (Jurnal Keguruan dan Ilmu Pendidikan), 2017)
This research intention is to observe and to know the increase of the students’ speaking ability in fluency at the second grade Exact students of SMA Muhammadiyah 7 Makassar for exactly 22 students joined as the samples. To run this researcht, the researcher applied Classroom Action Research (CAR). The step are Diagnostic test, test cycle I, and test cycle II. Before holding test cycle I and cycle II, the researcher administered action to the students through two cycles, there were  four meetings in every cycle. In cycle I test result had shown the improvement in the students speaking skill compared with the diagnostic test, it was 3.6 for fluency in the diagnostic test. However the improvement was still not complete the standard score which was 6.5, hence the researcher applied cycle II. In the test cycle II the students got the improvement significantly which was 7.6 in fluency.